The Law No. 20 of 2023: Reform or Retreat? A Critical Analysis of Its Impact on The State Civil Apparatus (ASN) Personnel System in Indonesia - Jawade Hafidz; Agus Prasetia Wiranto; Resa Ayuning Maharanti (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The enactment of Law No. 20 of 2023 concerning the State Civil Apparatus (ASN Law) marks a significant normative reconstruction in the governance of state civil servants in Indonesia. This law explicitly affirms the principles of meritocracy, professionalism, and bureaucratic modernization through digitalization and the structuring of the status of Civil Servants (PNS) and Government Employees with Work Agreements (PPPK). However, behind the rhetoric of reform, the ASN Law also contains problematic constitutional and administrative implications, particularly regarding central-regional relations, the legal status of PPPK, and the effectiveness of the merit system in stemming the politicization of the bureaucracy. This study uses a normative legal research method with a statutory and conceptual approach to analyze the consistency of the ASN Law with the principles of regional autonomy, equality before the law, and neutrality of state apparatus. The study results show that the ASN Law tends to reinforce the centralization of ASN management authority, creating formal but not substantive equality between PNS and PPPK, and placing the merit system in a vulnerable position to political co-optation due to the weak design of independent oversight. Thus, the ASN Law has the potential to give rise to what can be called functional unconstitutionality, namely a condition where legal norms appear to be textually aligned with the 1945 Constitution, but functionally weaken the constitutional principles they are intended to protect.